Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1109/access.2021.3105914
|View full text |Cite
|
Sign up to set email alerts
|

Training Neural Networks by Enhance Grasshopper Optimization Algorithm for Spam Detection System

Abstract: A significant negative impact of spam e-mail is not limited only to the serious waste of resources, time, and efforts, but also increases communications overload and cybercrime. Perhaps the most damaging aspect of spam email is that it has become such a major tool for attacks of cross-site scripting, malware infection, phishing, and cross-site request forgery, etc. Due to the nature of the adaptive unsolicited spam, it has been weakening the effect of the previous discovery techniques. This article proposes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…With each new generation, the MOBGOA algorithm generates new solutions (a new subset of features is generated). It is entered into the MLP that is trained by the best enhanced GOA (which is introduced in our previous work [41]). The method is employed by employing the novel feature set, and feedback on the method is obtained from the performance of the E2GOAMLP algorithm, which calculates the three objectives and arranges a new solution.…”
Section: ) Wrapper Feature Selection Methods Using Egoamlpmentioning
confidence: 99%
See 1 more Smart Citation
“…With each new generation, the MOBGOA algorithm generates new solutions (a new subset of features is generated). It is entered into the MLP that is trained by the best enhanced GOA (which is introduced in our previous work [41]). The method is employed by employing the novel feature set, and feedback on the method is obtained from the performance of the E2GOAMLP algorithm, which calculates the three objectives and arranges a new solution.…”
Section: ) Wrapper Feature Selection Methods Using Egoamlpmentioning
confidence: 99%
“…It is an evaluation procedure that begins with using the E2GOAMLP algorithm to train multilayered neural networks. The E2GOAMLP algorithm is better understood by the interested reader compared to earlier research [41]. The feature selection process is one of the most crucial processes, and the feature selection algorithm is based on a wrapper algorithm.…”
Section: B the Feature Selection Phase 1) Design Of Multi-objective B...mentioning
confidence: 99%
“…The use of reinforcement learning has been investigated for its ability to optimize spam detection strategies over time [42], [43], [15], [44], [45]. Studies have also shown the effectiveness of neural network architectures in detecting phishing websites, a common form of spam [46], [47], [48]. The application of AI for real-time spam detection in social media platforms has demonstrated promising results, highlighting the scalability of these models [15], [40].…”
Section: B Ai and Machine Learning Models In Spam Detectionmentioning
confidence: 99%
“…www.ijacsa.thesai.org Spam e-mail has several detrimental effects, including increased communications overload and cybercrime, as shown by the study of S. A. A. Ghaleb et al [7]. Spam email has become a key weapon for assaults such as cross-site scripting, malware infection, phishing, and cross-site request forgery, etc., which is the most dangerous feature of spam email.…”
Section: Parallel Recent Research Outcomesmentioning
confidence: 99%